Site-selective electrooxidation of methylarenes to aromatic acetals - Peng Xiong (Nature Portfolio, 2020)
Benzylic oxygenation of methylarenes is a direct but challenging method for aldehyde synthesis from simple starting materials. Here, the authors show an electrochemical, site-selective method for the oxidation of methyl benzoheterocycles to aromatic acetals without using chemical oxidants or transition metal catalysts.